Intervención educativa sobre lavado de manos como medida de prevención del COVID - 19 en comerciantes del mercado Belén de Iquitos 2021 - Sinarahua Mori, Wendy Stacy Jenifer (2022)
Hands are the route of transmission for cross-infection and some epidemic outbreaks and pandemics. For this reason, it is important to carry out an adequate Handwashing in a certain time to use the necessary implements such as soap and water to obtain an effective result. The objective is to evaluate the effect of the educational intervention on Handwashing as a preventive measure for COVID-19 in merchants of Mercado Belén 2021. The study is quantitative, the analytical design of a quasi-experimental type with pre and post evaluation with a single group, the population is made up of 273 merchants and the sample of 30 merchants from the areas of fish, meat and chicken, vegetables, prepared food, medicinal plants and grains. The technique is observation and the instruments are the observation guide (prepared by De la Cruz R, Pajuelo; Cronbach’s alpha reliability of ? = 0.939 and validity of r = 0.979), and the educational intervention. The results show that the Handwashing before the educational intervention 93.3% was incorrect and afterwards it decreased by 30%. To verify the hypothesis, the Wilcoxón Ranges statistical test was applied for related data that do not present a normal distribución, training p – value 0.000, the score of the observations rose significantly from 5.43 to 8.93, and the hypothesis. The work concludes that the educational intervention on Handwashing is effective.